Influence of Rust Removal Process on The Effectiveness of Sacrificial Anode Cathodic Protection in Repair Concrete. Issue 1 (May 2020) - Astuti, P; Kamarulzaman, K; Rafdinal, R S; Hamada, H; Sagawa, Y; Yamamoto, D
Abstract: The accumulation of corrosion product on the steel surface may cause eventual failure to deliver of ionic current protection from sacrificial anode cathodic protection. The effect of cleaning of deteriorated steel bar before cathodic protection application is studied in this paper. Two specimens having a length of 580 mm and 150x100 mm of the cross-sectional area with deteriorated reinforcing bar and half-part of chloride contaminated concrete were fabricated to simulate the repair process. Two corroded reinforcing bar with the same surface condition (ø 13mm) were embedded in concrete parallel to each other with the intermediary distance of 40 mm and the cover depth of 30 mm in the bottom surface of the specimen. In the first specimen, rust on the steel bar surface in the repair section was removed. Discrete sacrificial zinc anode is connected to one steel bar in the repair section. During three-years observation, the specimens were exposed to several conditions: 20°C air curing, dry-wet cycle, dry laboratory air, and wet condition, respectively. Potential of both rebar and the sacrificial anode was monitored to understand the performance of the cathodic protection system. The result indicates that rust removal process of steel bar surface in repair concrete part is the most desirable initial condition when the sacrificial anode is applied on it to protect corroded steel bar in new and existing concrete.